2018
DOI: 10.3390/ijms19061573
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivities of Phenolics by Focusing on Suppression of Chronic Diseases: A Review

Abstract: Phenolics, which are secondary metabolites of plants, exhibit remarkable bioactivities. In this contribution, we have focused on their protective effect against chronic diseases rather than their antioxidant activities, which have been widely discussed in the literature. A large body of epidemiological studies has proven the bioactivities of phenolics in both standard compounds and natural extracts: namely, anticancer, anti-inflammatory, and antibacterial activities as well as reducing diabetes, cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
186
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(220 citation statements)
references
References 104 publications
3
186
0
1
Order By: Relevance
“…In their study Mtunzi et al [59] ranked the activity of the plant crude extracts in the following order: ethyl acetate > dichloromethane > water > acetone > hexane [59]. Interestingly, high antioxidant activity in DPPH assays is associated with phenolic compound quantity in crude extracts [80,84,85] and this can be seen in our GC/ MS findings (Table 3) where several phenolic compounds were detected and identified.…”
Section: Antimicrobial Activity and Micmentioning
confidence: 59%
“…In their study Mtunzi et al [59] ranked the activity of the plant crude extracts in the following order: ethyl acetate > dichloromethane > water > acetone > hexane [59]. Interestingly, high antioxidant activity in DPPH assays is associated with phenolic compound quantity in crude extracts [80,84,85] and this can be seen in our GC/ MS findings (Table 3) where several phenolic compounds were detected and identified.…”
Section: Antimicrobial Activity and Micmentioning
confidence: 59%
“…Together, these observations indicate that members of this family produce compounds with therapeutic potential as growth inhibitors. This is not entirely surprising since phenolic compounds are generally believed to have anti-cancer properties [16,17].…”
Section: Effects Of Extracts From Specific Plant Families On Human Prmentioning
confidence: 99%
“…Interestingly, these roles include anticancer, anti-inflammatory, and antibacterial activities. To date, several thousand phenolic compounds have been isolated from a variety of plants including fruits, legumes, and cereals [16,17]. Plants produce alkaloids as secondary metabolites in response to stress.…”
Section: Phytochemicals and Traditional Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…These alcohols are also important and valuable in chemical synthesis as precursors of important drugs . Previous studies have shown that many derivatives of the hydroxycinnamic acid family are effective nutraceuticals with significant benefits for human health and can act as effective antioxidants with an important function as protective agents against chronic diseases . Therefore, diets including fruits and vegetables are strongly recommended.…”
Section: Introductionmentioning
confidence: 99%